Pengaruh Gaya Kepemimpinan, Lingkungan Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan : Studi PT. Sukanda Djaya Cabang Ancol - Wicaksono, Hari Murti; Tarmizi, Achmad (Prisani Cendekia, 2024)
The purpose of this study is to examine the efforts of PT Sukanda Djaya, Ancol branch, a food and beverage distribution company headquartered in Bekasi, in improving employee performance for optimal work outcomes. Declining employee performance has resulted in decreased delivery of goods to customers due to loading errors and violations of the FIFO principle. The research identifies three factors contributing to the decline in performance: ineffective leadership style, work environment affecting job completion time, and lack of job satisfaction. This study employs a quantitative approach with data analysis techniques using statistics through IBM SPSS Statistics Version 26 to manage data collected from FG warehouse employees of PT Sukanda Djaya, Ancol branch, using saturated sampling. To obtain primary data, data collection is conducted using questionnaires distributed to FG warehouse employees of PT Sukanda Djaya, Ancol branch, who can support this research. The findings of this study indicate a significant influence between leadership style, work environment, and job satisfaction on employee performance.